(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to analyze in the existing literature the benefits of exclusive breastfeeding until the sixth month of life. Methods: integrative review of the literature, based on articles through the Virtual Health Library (VHL), through the electronic databases: Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature in Sciences (LILACS), with the year of publication between 2013 and 2018. Results: the search in the databases consulted resulted in 82 articles, but 18 were defined for analysis. Thus, after analyzing the studies, three categories were defined for the discussion of the results: Benefits of Exclusive Breastfeeding until the sixth month of life, Factors that lead to the early weaning of Breastfeeding and Actions developed by nurses in the promotion of breastfeeding. Conclusion: It was evidenced that breastfeeding is a complete and irreplaceable food, directly reflecting the quality of life of the mother and the infant. And, that nursing is fundamental in encouraging this practice.